Seni Kriya Tekstil Teknik Punch Needle Sebagai Upaya Pelestarian Makanan Tradisional Jawa Barat yang Sudah Punah - MC Wara Candrasari; Rahmawati Rahmawati; Elita Nur Ilahi; Febby Bunga Permata Sumardi (Universitas Sultan Ageng Tirtayasa, 2026)
Traditional Indonesian foods, including those found in West Java, are an important part of cultural identity and local heritage. However, traditional Indonesian cuisine is becoming endangered, according to Mei Batubara, Chair of the Pusaka Rasa Nusantara Team, due to a lack of regeneration in the ability to cook traditional foods. This study aims to highlight endangered traditional West Javanese foods in a different form in the field of Art Education. The application of this research in the world of education provides an opportunity to reintroduce cultural values through arts-based learning. The methods used are a qualitative descriptive approach and the results of a literature review analysis involving interviews with the younger generation and observations at major culinary destinations. Previous research in 2024 mentioned that many people, especially young people, prefer fast food because it is considered more practical and more contemporary than traditional Indonesian food. Additionally, according to the Head of the Pusaka Rasa Nusantara Team, Mei Batubara, the reason traditional Indonesian cuisine is disappearing is due to the lack of regeneration in those who can cook traditional food. The disappearing traditional foods of West Java became the inspiration for preservation efforts, transforming them into textile artworks using the punch needle technique. Through punch needle learning, art education becomes a space to introduce traditional culinary delights, so that the existence of typical West Javanese food is not only studied theoretically, but also experienced and preserved through artistic practices that are relevant to the younger generation, It can even be useful in developing models in the world of education